2001
DOI: 10.2307/3871417
|View full text |Cite
|
Sign up to set email alerts
|

Novel Filaments 5 nm in Diameter Constitute the Cytosolic Ring of the Plastid Division Apparatus

Abstract: The plastid division apparatus (called the plastid-dividing ring) has been detected in several plant and algal species at the constricted region of plastids by transmission electron microscopy. The apparatus is composed of two or three rings: an outer ring in the cytosol, an inner ring in the stroma, and a middle ring in the intermembrane space. The components of these rings are not clear. FtsZ, which forms the bacterial cytokinetic ring, has been proposed as a component of both the inner and outer rings. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…First, they indicate that FtsZ2 is not a component of the outer PD ring. This is consistent with a recent report by Miyagishima et al (2001) indicating that FtsZ could not be detected in outer PD ring extracts from red algae. Based on these and other data, these investigators hypothesized that the outer PD ring is not derived from the endosymbiotic progenitor of chloroplasts, as are the FtsZ rings, but rather from the host cell.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, they indicate that FtsZ2 is not a component of the outer PD ring. This is consistent with a recent report by Miyagishima et al (2001) indicating that FtsZ could not be detected in outer PD ring extracts from red algae. Based on these and other data, these investigators hypothesized that the outer PD ring is not derived from the endosymbiotic progenitor of chloroplasts, as are the FtsZ rings, but rather from the host cell.…”
Section: Discussionsupporting
confidence: 83%
“…However, inconsistent with the hypothesized localization of FtsZ2 in the outer PD ring, subsequent submissions of other plant FtsZ2 sequences revealed that the extreme amino termini of most FtsZ2 family members, including AtFtsZ2-2, were longer than that predicted for AtFtsZ2-1 (Osteryoung and McAndrew, 2001), suggesting that the AtFtsZ2-1 ORF used in our previous analysis (Osteryoung et al, 1998) might be incomplete, lacking the transit peptide. In addition, two recent studies demonstrated that nuclearencoded FtsZ2-like proteins from the moss Physcomitrella patens were localized in the chloroplast when expressed as green fluorescent protein fusion proteins in vivo (Kiessling et al, 2000) and that FtsZ could not be identified immunologically in outer PD ring preparations from red algae (Miyagishima et al, 2001). Furthermore, genes encoding both FtsZ1 and FtsZ2 proteins have only been identified in higher plant genomes; thus, the relationship of the findings in moss and algae to the organization of the plastid division apparatus in higher plants remains unclear.…”
mentioning
confidence: 99%
“…Interestingly, the topology of the ARC5-containing ring is similar to that of the outer PD ring (15,50). Like ARC5, which lacks homologues in cyanobacteria and was probably derived from the eukaryotic host cell, the outer PD ring has been proposed to be of eukaryotic origin (19).…”
Section: Discussionmentioning
confidence: 79%
“…The protein machine of chloroplasts, unlike that of bacteria, can be observed in electron micrographs of thin sections. One possible reason for its visibility is that this machine consists of at least three layers: an innermost ring comprising FtsZ, followed by the plastid dividing ring that is visible by negative staining but is of unknown composition 102 , and an outermost ring on the outside of the organelle that contains a dynamin-like protein (DRP) 103,104 . Dynamins are eukaryotic GTPases that assemble on membranes and mediate membrane fission 97 ; dynamin also has a role in cytokinesis of animal and plant cells 105,106 .…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%